Analysis of respirable dust exposure data collected at a Zambian copper mine between 2017 and 2022 - Mwaba Sifanu; Kennedy K. Kalebaila; Patrick Hayumbu; Lubinda Nabiwa; Stephanus J. L. Linde (Frontiers Media S.A., 2024)
Mine workers are occupationally exposed to respirable dust, which can cause irreversible lung diseases and controlling exposure concentrations to as low as reasonably practicable is, therefore, essential. To implement exposure reduction strategies and adequately manage exposure to hazardous chemicals, exposure needs to be measured and recorded according to a standard exposure management plan. This study aimed to assess the available respirable dust exposure data measured between 2017 and 2022 in various work areas and job categories at two mining shafts and a concentrator plant of a Zambian copper mine. Additionally, the monitoring program implemented at the mine was assessed for appropriateness. Descriptive data analysis was used to create an exposure matrix comprising 253 exposure measurements. Approximately 5.6% of the measured concentrations exceeded the South African time-weighted average occupational exposure limit (TWA-OEL) of 3 mg/m3. The geometric means of respirable dust exposure for shaft A, shaft B and the concentrator plant were 0.44 mg/m3, 0.44 mg/m3, and 0.68 mg/m3, respectively. The work areas with the highest maximum exposure results were the tipping area (18.0 mg/m3) at shaft A, the sump and waste bin (8.05 mg/m3) at shaft B and the screening (10.8 mg/m3), secondary crusher (14.0 mg/m3), foreign ore bin (4.43 mg/m3), and tertiary crusher (5.07 mg/m3) areas at the concentrator plant. It was found that the monitoring strategy implemented at the mine was flawed and did not collect a sufficient number of samples in each area during each year to make rigorous statistical assessment possible. This study highlights the sampling strategy's shortcomings and recommends adopting a standardized monitoring strategy, such as EN689, to improve the respirable dust monitoring program at the mine. Additionally, this strategy can be implemented across Zambia and, if implemented correctly, it has the potential to be improve exposure monitoring across the country as no standard sampling strategy is currently enforced by the Government.